World literature(s). Traduzioni e storia letteraria nazionale - Sisto, Michele (Status Quaestionis, 2024)
If world literature is primarily constituted through translations, it cannot be conceived as a unitary repertoire but rather as a plurality of repertoires: indeed, through the act of translation, diverse national cultures produce an equal number of world literatures. Drawing upon recent advancements in comparative literature and translation studies, this essay explores the possibility of rewriting literary history—beginning with the case of Italian literature—by structurally incorporating translated literature.